The environmental degradation behavior of FeNiMnCr high entropy alloy in high temperature hydrogenated water. (November 2021) - Dong, Jiuyang; Feng, Xingyu; Hao, Xianchao; Kuang, Wenjun
Abstract: Co-free high entropy alloy (HEA) 28%Fe-27%Ni-27%Mn-18%Cr shows good irradiation resistance and could be a potential candidate for structural material in nuclear power industry. In this work, the environmental degradation behavior of this HEA was investigated in high temperature hydrogenated water. This HEA shows extensive intergranular cracking after constant extension rate tensile test, indicating that it is very susceptible to stress corrosion cracking (SCC) initiation. The microstructure analysis indicates that Mn and Cr diffuse outwards along the grain boundary during oxidation, inducing grain boundary migration. The Cr flux promotes the formation of Cr-enriched oxide layer above the grain boundary which prevents intergranular oxidation when the sample is unstressed. However, Mn is unstable in the oxide and tends to dissolve into the solution, making the oxide porous. The porous oxide fractures readily when stressed, inducing SCC initiation. Graphical abstract: Image, graphical abstract